Effect of Different Vacuum Cooling Methods on the Qualities of Different Parts of Water-cooked Pork - Chen Hua; Liu Baolin; Song Xiaoyan; Liu Yang (Zhileng xuebao)
Vacuum cooling (VC) and immersion vacuum cooling (IVC) were carried out to explore their effects on the quality of different parts of water- cooked pork. The weight loss, cooling rate and qualities (pH, color and TPA) of different parts of the meat were measured after cooling. Results showed that IVC could achieve a lower weight loss (P<0.05) compared to VC. However, a better temperature uniformity of the sample was found during VC compared to IVC. Both the brightness and redness values of the central and internal parts have not presented significant differences (P>0.05) between the samples undergone VC and IVC respectively. However, IVC can increase the lightness value of the external part significantly (P<0.05) compared to VC. Both the hardness values and chewiness values of both the central and internal parts were significantly reduced (P<0.05) after IVC, while there was no significant difference between the samples treated by VC and IVC respectively for the springiness and resilience values of all locations inside samples except external part.